Approach for predicting effective thermal conductivity of aerogel materials through a modified lattice Boltzmann method. (5th March 2018) - Qu, Z.G.; Fu, Y.D.; Liu, Y.; Zhou, L.
Highlights: Approach is proposed to predict effective thermal conductivity of aerogel materials. Random micro aerogel porous structure is reconstructed and mimicked. The method offers improved prediction accuracy than theoretical models. Effects of density, pressure and temperature on insulation performance are obtained. Abstract: A modified lattice Boltzmann method (LBM) is established to predict effective thermal conductivity of aerogel materials for insulation performance. A stochastic generation method based on mesoscopic solid-phase growth principle is adopted to reconstruct and mimic aerogel porous structure. The modified LBM scheme introduces an additional coefficient to regulate significant differences in inherent thermal conductivity between solid and gas phases, and a converged solution is guaranteed. The modified model is validated with experimental data, and it offers improved prediction accuracy than conventional theoretical models. Investigations are performed to determine the effects of density, ambient pressure, and characteristic temperature on effective thermal conductivity. When temperature is lower than 500 K, an optimal density of 110 kg/m 3 minimizes effective thermal conductivity. When temperature is higher than 500 K, the effective thermal conductivity decreases monotonously with increasing density. At fixed temperature, the variation in effective thermal conductivity can be divided into three typical stages based on pressure. Separate contributions of gas-phase conduction, solid-phase conduction, and radiative heat transfer are discussed and analyzed.